Balancing WNT signalling in early forebrain development: The role of LRP4 as a modulator of LRP6 function - Geng, Shuang; Paul, Fabian; Kowalczyk, Izabela; Raimundo, Sandra; Sporbert, Anje; Mamo, Tamrat Meshka; Hammes, Annette (Frontiers in Cell and Developmental Biology, 2023)
The specification of the forebrain relies on the precise regulation of WNT/ß-catenin signalling to support neuronal progenitor cell expansion, patterning, and morphogenesis. Imbalances in WNT signalling activity in the early neuroepithelium lead to congenital disorders, such as neural tube defects (NTDs). LDL receptor-related protein (LRP) family members, including the well-studied receptors LRP5 and LRP6, play critical roles in modulating WNT signalling capacity through tightly regulated interactions with their co-receptor Frizzled, WNT ligands, inhibitors and intracellular WNT pathway components. However, little is known about the function of LRP4 as a potential modulator of WNT signalling in the central nervous system. In this study, we investigated the role of LRP4 in the regulation of WNT signalling during early mouse forebrain development. Our results demonstrate that LRP4 can modulate LRP5- and LRP6-mediated WNT signalling in the developing forebrain prior to the onset of neurogenesis at embryonic stage 9.5 and is therefore essential for accurate neural tube morphogenesis. Specifically, LRP4 functions as a genetic modifier for impaired mitotic activity and forebrain hypoplasia, but not for NTDs in LRP6-deficient mutants. In vivo and in vitro data provide evidence that LRP4 is a key player in fine-tuning WNT signalling capacity and mitotic activity of mouse neuronal progenitors and of human retinal pigment epithelial (hTERT RPE-1) cells. Our data demonstrate the crucial roles of LRP4 and LRP6 in regulating WNT signalling and forebrain development and highlight the need to consider the interaction between different signalling pathways to understand the underlying mechanisms of disease. The findings have significant implications for our mechanistic understanding of how LRPs participate in controlling WNT signalling.